The Coating of Mahogany Leaves Composite Using Clove Leaf Essential Oil as An Anti-Fungal Ganoderma lucidum - Masturi, Masturi; Alighiri, Dante; Anwar, Ahmad Faisal; Choirunnisa, Fadhillah; Kirana, Kurnia Galuh Candra (Universitas Jember, 2023)
This work has been carried out to use clove leaf oil as a composite coating component having anti-fungal properties. The mushroom growth testing was carried out with minimum inhibitory concentration (MIC) testing with variations in concentrations of 0%, 0.2%, 0.4%, 0.6%, 0.8%, up to 1% and obtained MIC values of clove oil found at a concentration of 0.4% in inhibiting the growth of white-rot fungi. Ganoderma lucidum mushroom is used as a weathering fungus applied in composites. The results of SSD testing showed that the growth of Ganoderma lucidum fungus began to be inhibited in composites coated with clove oil with a concentration of 0.6%.FTIR testing showed the presence of hydroxyl group (O-H), methylene group (C-H), alkenyl (C=C), and aromatic ring (C=C-C), GC-MS test results showed clove oil containing 67.40% eugenol, 17.42% beta-caryophyllene, 2.91% isopropenyl acetate, 1.56% caryophyllene oxide and 0.91% alpha-copaene. Based on research data, it shows that clove leaf oil can be used as an anti-fungal coating component in composites.